Examining school librarians'readiness for information literacy implementation - Tan, S.M.; Kiran, K.; Diljit, S. (2014)
This study investigates how school librarians perceive their readiness in implementing information literacy (lL) education in schools. It addresses the concerns that school librarians are not adequately prepared in delivering the IL programme in secondary schools. This study uses a quantitative research design with two distinct data collection techniques; a semi structured interview and a survey involving 710 school librarians from secondary schools in Malaysia. School librarians' readiness construct is derived from the cognitive, functional and technical sub-scales of IL implementation readiness. School librarians' professional qualification has an impact on their cognitive, functional and technical readiness. However, their experience as a school librarian has an impact on technical readiness only. The study proposes an IL Implementation framework that emphasizes School Librarians' Readiness as a factor to the successful implementation of ILE in Malaysian schools.